IDENTIFIKASI PENGETAHUAN PERAWAT GAWAT DARURAT TENTANG TRIAGE - Vicky Setiarini; Wan Nishfa Dewi; Darwin Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The Emergency Room (IGD) in handling the emergency patient has triage system for doing emergency action. Triage is the process which choose the patient according the turbulence level and in the handling the patient become priority. One of the successful factor in handling the emergency case is triage knowledge. This study aims to determine for doing identification of nurses emergency knowledge about triage. This study was doing in the IGD RSUD Arifin Achmad room. This study was used the descriptive research. The sample of this study is nurse in IGD with 31 people thourgh total sampling teachnique. The data was collected with using questionnaire that has been validity and reliability test. This study used descriptive analysis. The result of the study showed that the nurse has a good knowledge as much 51,6%. Based on the result of the research, the researcher give the suggestion to the nurse to improve the quality of emergence services. Keywords: Emergency, IGD, knowledge, nurses, triage